Initial clinical experience and biomechanical analysis of a novel gravity unit-assisted valve (M.blue) in pediatric patients with hydrocephalus: a retrospective study with two years of follow-up - Issa, Mohammed; Paggetti, Filippo; Seitz, Angelika; von Hardenberg, August; Unterberg, Andreas; El Damaty, Ahmed (Neurosurgery, 2023)
BACKGROUND: - Overdrainage is a widely reported complication representing common indication for shunt revision. Despite recent advances in valve design, repeated shunt revisions represent burden on healthcare systems. - OBJECTIVE: - To investigate the efficiency of a novel gravity unit-assisted programmable valve “M.blue” in pediatric hydrocephalus using clinical and biomechanical analyses. - METHODS: - Thisretrospective single-center study included pediatric patients who received M.blue valve between April 2019 and 2021. Several clinical and biomechanical parameters were documented including complications and revision rates. Flow rate, functional assessment in vertical and horizontal positions, and extent of depositions inside valve were analyzed in explanted valves. - RESULTS: - Thirty-seven M.blue valves in 34 pediatric patients with hydrocephalus (mean age 2.82 ± 3.91 years) were included. Twelve valves (32.4%) were explanted during a follow-up period of 27.3 ± 7.9 months. One-year survival rate of 89% and overall survival rate of 67.6% with a valve survival average of 23.8 ± 9.7 months were observed. Patients with explanted valves (n = 12) were significantly younger, with 0.91 ± 0.54 years of age in average (P= .004), and showed significantly more adjustments difficulties (P= .009). 58.3% of explanted valves showed deposits in more than 75% of the valve surface despite normal cerebrospinal fluid findings and were associated with dysfunctional flow rate in vertical, horizontal, or both positions. - CONCLUSION: - The novel M.blue valve with integrated gravity unit is efficient in pediatric hydrocephalus with comparable survival rate. Deposits inside valves could affect its flow rate in different body positions and might lead to dysfunction or difficulties in valve adjustments.